HIV testing in patients presenting with indicator conditions in outpatient settings: offer and uptake rates, and educational and active interventions. (November 2018) - Youssef, Elaney; Sanghera, Tanjinder; Bexley, Andrew; Hayes, Madeleine; Perry, Nicky; Dosekun, Olamide; Perera, Sean
Approximately 13% of people living with HIV in the UK are undiagnosed which has significant implications in terms of onward transmission and late diagnosis. HIV testing guidelines recommend routine screening in anyone presenting to healthcare with an HIV indicator condition (IC); however, this does not occur routinely. This study aimed to assess the feasibility and effectiveness of using case note prompts highlighting the presence of an IC to increase HIV testing. Clinicians in three outpatient departments received case note prompts either before or after a period of clinician-led identification. Test offer and uptake rates were assessed. A parallel anonymous seroprevalence study estimated the prevalence of undiagnosed HIV. A total of 4191 patients had an appointment during the study period; 608 (14.5%) had an IC. HIV test offer was significantly higher when a prompt was inserted into notes (34.3% versus 3.2%, p < 0.001). The prevalence of diagnosed HIV in the cohort was 4.1%. No cases of undiagnosed HIV infection were identified. Despite guidelines, offer of HIV testing is low. Strategies to increase routine screening of patients presenting with an IC are needed. Individual case note prompts significantly increase HIV test offer; however, the effect is lost if the strategy is withdrawn.